Medical surveillance on the staff of UiTM Pahang / Zainul Akramin Kambali, Pauzi Ibrahim, Khadijah Daud and Noorshaliza Sakyon Mohammad Notan - Ibrahim, Pauzi; Daud, Khadijah; Sakyon, Noorshaliza (Universiti Teknologi MARA, Jengka, 2007)
The phase one of structured and continuous medical surveillance programme was conducted on all staff of Universiti Teknologi MARA (UiTM) Pahang. The main objectives of the surveillance are to inculcate a healthy lifestyle and monitor the health risks among the staff of UiTM. A total of 325 staff (65%) participated in this programme. It was held at the Medical Unit of UiTM Pahang from 5th to 26th June 2007. The findings reveal that 47 participants (14%) were obese while 154 (48%) were overweight. A total of 210 participants (64.6%) had the cut off point of systolic pressure 140mmHg or more and diastolic pressure 90 mmHg or more. Diabetes with fasting glucose 7.9mmol/l or more was detected in 15 participants (6.6%). 67 or 45% of the participants were found to have elevated fasting cholesterol of 5.2 mmol/l or more. 5 participants (17%) were found to have significantly abnormal ECG. All participants detected to have health problems and illness were counseled and treated accordingly, and some were referred to the appropriate disciplines for further management.